Three-Dimensional Modeling of Hydrodynamics and Biokinetics in EGSB Reactor - Jixiang Yang; Yanqing Yang; Xin Ji; Youpeng Chen; Jinsong Guo; Fang Fang (Journal of Chemistry)
A three-dimensional model integrating computational fluid dynamics (CFD) and biokinetics was established to model an expanded granular sludge bed (EGSB) reactor in this study. The EGSB reactor treating synthesized municipal wastewater was operated at ambient temperature. The model provided satisfactory modeling results regarding hydrodynamics and biokinetics. The model shows that influent distribution was evenly distributed. In addition, butyrate and propionate degradation rates linearly decreased along the flow direction in the reactor. However, acetate degradation rate increased first and decreased later. VFA degradation rate distributions were different at each reactor cross section. VFA degradation rates near reactor wall were lower than VFA degradation rates at reactor axis. Moreover, a pulse high influent COD concentration had a tiny impact on effluent quality, which indicates that the reactor was stable while treating synthesized wastewater at adopted conditions.